Developing and delivering a hybrid Cardiac Rehabilitation Phase II exercise program during the COVID-19 pandemic: a quality improvement program - Poonam Gupta; Prasobh Jacob; Javier Loureiro Diaz; Liam David Foster; Praveen Jayaprabha Surendran; Omar Ibrahim (BMJ Open Quality)
The COVID-19 pandemic resulted in the cessation of approximately 75% of cardiac rehabilitation (CR) programmes worldwide. In March 2020, CR phase II (CRP2) services were stopped in Qatar. Multiple studies had shown safety, effectiveness, reduced cost of delivery and improved participation with hybrid CR. A multidisciplinary team reviewed various alternative models for delivery and decided to implement a hybrid CRP2 exercise programme (HCRP2-EP) to ensure continuation of our patient care. Our aim was to enrol in the HCRP2-EP 70% of all eligible patients by 30 September 2020. Institute for Health Care Improvement’s collaborative model was adopted. Multiple plan–do–study–act cycles were used to test change ideas. The outcomes of the project were analysed using standard run chart rules to detect the changes in outcomes over time. This project was implemented from March 2020, and the male patients enrolled between August 2020 and April 2021, with sustained monthly median enrolment above target of 70% throughout. As for our secondary outcome, 75.8% of the male patients who completed HCRP2-EP showed a meaningful change in peak exercise capacity of ≥10% (mean change 17%±6%). There were no major adverse events reported, and the median Patient Satisfaction Score was 96% well above the institutional target of 90%. This shows a well-designed quality improvement programme is an appropriate strategy for implementing HCRP2-EP in a clinical setting, and HCRP2-EP is a feasible, effective and safe intervention in eligible male patients with cardiovascular disease.